Fresno County Department of Social Services Reception for Linda Orante - Watkins, Howard::::::::: (1989)
Fresno County Department of Social Services Director Ernie Velasquez, In-coming Director Linda Orante, Fresno County Supervisor Sharon Levy and Judge Gary Austin